Genome-wide identification and characterization of Ethylene-Insensitive 3 (EIN3/EIL) gene family in Camellia oleifera - Shihang Huang; Fang Li; Caiqin Li; Xiaobei Li; Qiuling Pan; Yongquan Li; Wenpei Song; Juan Li (PLoS ONE, 2025)
Camellia oleifera, a vital woody oil crop in China, suffers substantial yield losses due to frequent physiological fruit abscission during cultivation. Ethylene signaling, mediated by Ethylene-Insensitive3/Ethylene-Insensitive 3-like (EIN3/EIL) transcription factors encoded by a multigene family, plays a pivotal role in plant organ abscission. However, the EIN3/EIL family remains understudied in C. oleifera. Here, genome-wide analysis identified four CoEIL genes encoding proteins with conserved EIN3 domains. Phylogenetic classification grouped these proteins into Group A and Group B, revealing evolutionary proximity between C. oleifera and tea (Camellia sinensis). Cis-acting regulatory element analysis implicated CoEIL genes in hormone responsiveness and stress adaptation. Quantitative real-time PCR analysis was performed to investigate the expression patterns of these CoEIL genes in the fruit abscission zone following ethephon and brassinolide treatments. This study elucidates the genetic architecture and functional divergence of CoEIL genes, laying the foundation for exploring molecular mechanisms of abscission in C. oleifera.